PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEMALSUAN TANDA NOMOR KENDARAAN BERMOTOR DI KOTA PEKANBARU - M REZKY RAMADHAN; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Legal certainty without being based on the joints of justice will causedissatisfaction and invite many reactions. The law functions as a social control(social control) can be interpreted, namely as a process whether planned or not,which is educational, inviting or even forcing citizens to comply with theprevailing system of rules and values. At this time in the city of Pekanbaru, therewere many perpetrators of the Counterfeiting of Motorized Vehicle Number Signs(TNKB). According to Article 263, namely: "Anyone who makes a fake letter orfalsifies a letter that can give rise to rights, commitments or debt relief, or whichis intended as evidence of something with the intent to use or order someone elseto use the letter as if the contents are true and not forged, threatened if the usecould cause harm, due to falsification of th e letter, with a maximumimprisonment of six years. " Threatened with the same crime, anyone whodeliberately uses fake letters or falsified as if it were true, if the use of the lettercan cause harm.The writing of this scientific paper aims to: first, how is the law enforcementof falsified vehicle markings in Pekanbaru. Second, to find out what are theobstacles in the process of law enforcement for the falsification of motor vehiclemarkings in Pekanbaru. Third, to find out how to overcome the counterfeiting ofvehicle number signs in Pekanbaru.From the results of this research, it can be concluded that theimplementation of criminal law enforcement against falsification of motorizedvehicle number sign (TNKB) in Pekanbaru City is carried out by the PekanbaruCity Police Department through 2 (two) efforts, namely, Preventive efforts carriedout by providing socialization to the wider community, especially to fake licenseplate users on Motorized Vehicle Number Signs, and with repressive measures,namely by giving a reprimand and issuing a ticket to the perpetrators of fake plateviolations of Motorized Vehicle Number Signs.Keywords: Criminal Acts, Counterfeiting, Vehicle Number Signs